Βραβείο Χριστίνα Ζιούρδου - Miltiadous, Panagiota (My University, 2026)
Βραβείο Χριστίνα Ζιούρδου στο συνέδριο της Ελληνικής Εταιρίας Νευροτροπισμών τίτλος “Neuronal Stem Cells can Survive, Migrate and Differentiate after Intrahippocampal Transplantation in adult mice following Kainic Acid Administration”
Keywords: Sciences